1997
DOI: 10.1111/j.1440-1738.1997.tb00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional metamorphic belts of the Japanese Islands

Abstract: An overview of the regional metamorphic belts of Japan is given in the context of the tectonic evolution of the Japanese Islands. The Japanese Islands were situated on an active margin of the Eurasian continent or its constituent landmass before their assembly during the Phanerozoic. The Japanese Islands are composed mainly of metamorphosed and unmetamorphosed accretionary complexes, granitoids and their effusive equivalents that were formed by the Cordilleran-type orogeny. The metamorphic belts are regarded e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 119 publications
1
51
0
Order By: Relevance
“…5). Nakajima (1997) suggested that the area of activated seismicity was associated with an area of high-pressure metamorphism, and is geologically different from the surrounding area. This indicates that the distribution of seismicity may be partitioned by the presence of numerous tectonic blocks, with the N-S σ 1 stress field within the area of activated seismicity potentially being caused by local stress-field variations relating to the heterogeneous structure of this area.…”
Section: Resultsmentioning
confidence: 99%
“…5). Nakajima (1997) suggested that the area of activated seismicity was associated with an area of high-pressure metamorphism, and is geologically different from the surrounding area. This indicates that the distribution of seismicity may be partitioned by the presence of numerous tectonic blocks, with the N-S σ 1 stress field within the area of activated seismicity potentially being caused by local stress-field variations relating to the heterogeneous structure of this area.…”
Section: Resultsmentioning
confidence: 99%
“…The dominant lithology is bioturbated silty claystone with abundant interbeds of dark gray clayey siltstone (deposited by muddy turbidity currents) and fine-grained siliciclastic sandstone (deposited by sandy turbidity currents). We suggest that the most likely terrigenous sources for this sandy detritus were rock units now exposed across the Outer Zone of southwest Japan, including the Shimanto Belt (Taira et al, 1989;Nakajima, 1997). Superficially similar sand deposits, with overlapping ages, have been documented on the southwest side of the Shikoku Basin at ODP Site 1177 and DSDP Site 297 offshore the Ashizuri Peninsula of Shikoku (Marsaglia et al, 1992;Fergusson, 2003;Underwood and Fergusson, 2005).…”
Section: Principal Results From Site C0011mentioning
confidence: 99%
“…Usually, however, with the exception of the elements of the proto-Japan superterrane, most terranes oceanward of the Hida-Oki terrane, are interpreted as subduction-accretion complexes formed due to the subduction of lithosphere of different oceanic basins below the proto-Asian continent since the early Palaeozoic (Isozaki 1997a(Isozaki , 1997bMaruyama et al 1997;Nakajima 1997;Ernst et al 2007). Such complexes are composed of trench fill or fore-arc sediments and oceanic components, like chert, (pillow) basalt and limestone, that is, former reef caps of seamounts (Isozaki 1997a, b;Maruyama et al 1997;Nakajima 1997;Wakita and Metcalfe 2005). Especially during the Jurassic to Early Cretaceous, extensive accretion took place including the Mino-Tamba-Ishio terrane, the Northern Chichibu terrane, the North Kitakami terrane, as well as the protoliths of the Mikabu and Sambagawa belts (Isozaki 1997a, b;Nakajima 1997;Suzuki and Ogane 2004;Wakita and Metcalfe 2005).…”
Section: Regional Tectonic Framework Of the Japanese Islandsmentioning
confidence: 99%
“…2) have been compared to this terrane (Kaneoka et al 1996). Commonly, the metamorphic rocks of the main Hida belt of central Japan are regarded as belonging to the North China craton, and the Oki metamorphics as part of the South China craton (Sohma et al 1990;Banno and Nakajima 1992;Isozaki 1997a;Maruyama et al 1997;Nakajima 1997;Ernst et al 2007). Consequently, the Middle-Late Triassic Qinling-Dabie-Sulu suture between both the cratons was considered to continue into the Japanese region (Maruyama and Seno 1986;Isozaki 1997a;Maruyama 1997;Maruyama et al 1997;Ernst et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation